2019
DOI: 10.1136/ijgc-2019-000609
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of PD-1 and PD-L1 positive tumor-infiltrating immune cells in ovarian carcinoma

Abstract: IntroductionOvarian carcinoma is associated with the highest mortality of all gynecologic malignancies. Even after optimal treatment, prognosis remains poor. There is no established biomarker to predict individual patient outcome.ObjectiveTo evaluate the prognostic significance of PD-1 and PD-L1 expression in tumor tissues from patients with ovarian cancer.MethodsTissue micro-arrays were prepared from routinely formalin-fixed, paraffin-embedded tumor tissues and examined immunohistochemically for the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…Furthermore, the prognostic significance of PD-L1 in EOC is debatable. Several studies have reported that high levels of PD-1 or PD-L1 are indicators of favorable prognosis [ 51 , 52 , 53 , 54 ]. Specifically, Webb et al found PD-L1 to be associated with higher levels of tumor infiltrating lymphocytes (TILs).…”
Section: Challenges To Pd-1 Therapymentioning
confidence: 99%
“…Furthermore, the prognostic significance of PD-L1 in EOC is debatable. Several studies have reported that high levels of PD-1 or PD-L1 are indicators of favorable prognosis [ 51 , 52 , 53 , 54 ]. Specifically, Webb et al found PD-L1 to be associated with higher levels of tumor infiltrating lymphocytes (TILs).…”
Section: Challenges To Pd-1 Therapymentioning
confidence: 99%
“…These immune cells can subsequently have a tumor cell action. 9 It has recently been suggested that the presence of intratumoral inflammatory infiltration associated with PD-L1 expression influences survival in HGSC 10,11 with clinical trials using anti-PD-L1 immunotherapy such as pembrolizumab and avelumab showing promising results. 6,[12][13][14][15] Two recent meta-analysis suggested that PD-L1 expression was not linked to tumor histology, overall survival (OS), and progressionfree survival (PFS), but that PD-L1 mRNA expression was closely correlated with poor PFS.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting result of our study is the association of PD-L1 expression on chondrosarcoma cells in primary tumors with shorter time to metastatic spreading. Caution has to be exercised in interpreting this finding because the number of tumor samples analysed is small, however in other cancers PD-L1 expression has been associated with metastatic disease (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%